RELATIONSHIP BETWEEN THE COMPONENTS OF HEAD NURSES MANAGEMENT CAPACITY AND INFLUENCING FACTORS: A CASE STUDY IN VIETNAM - Uy, Nguyen Van; Oanh, Thai Thi Kim; Huyen, Nguyen Thi Ngoc (The journal of contemporary issues in business and government, 2021)
The study is based on Chase 1994's approach to management capacity of head nurses and uses linear regression analysis to determine the relationship between the components of head nurses' management capacity with other influencing factors. The results show that factors such as age, seniority of management, degrees, seniority of work, and management degrees explain 39.1% of the change in professional capacity and 56% of the change in professional competence explaining 52% of the change in thinking ability, explaining 33% of the change in leadership skills and explaining 34% of the change in management skills of financial management. The relationship between management seniority and professional skills is statistically significant and negatively correlated. The relationship between qualifications, working seniority and human resource management skills is statistically significant and positively correlated. The relationship between qualifications, management degrees and thinking skills of head nurses is statistically significant and positively correlated. In addition, the research results also show that the relationship between the influencing factors and the components of the management capacity of head nurses is not statistically significant.